Literasi Keuangan dan Keberlanjutan UMKM: Mediasi Ketangguhan Kewirausahaan dan Akses terhadap Keuangan - Rani Utrojah; Nila Aprila; Deddy Susanto (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the effect of financial literacy on MSMEs’ business sustainability, with entrepreneurial resilience and access to finance serving as mediating variables among MSMEs in Bengkulu City. The population of this study comprises 34,600 registered and active MSMEs in Bengkulu City. Using purposive sampling with criteria that MSMEs have been operating for at least two years and maintain financial records, a total of 120 respondents were selected. This research adopts a quantitative approach, collecting data through structured questionnaires and analyzing them using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results demonstrate that financial literacy has a positive and significant effect on entrepreneurial resilience, access to finance, and business sustainability. Furthermore, entrepreneurial resilience and access to finance both exert positive and significant effects on business sustainability. Mediation analysis confirms that entrepreneurial resilience and access to finance significantly mediate the relationship between financial literacy and business sustainability. These findings indicate that financial literacy plays a strategic role not only in strengthening internal entrepreneurial capacity but also in improving MSMEs’ ability to access external financial resources, which collectively enhance business sustainability. Therefore, efforts to improve MSMEs’ sustainability in Bengkulu City should emphasize comprehensive financial literacy development that integrates financial management skills, psychological resilience, and financial inclusion to ensure long-term business viability and competitiveness.